The Tradition of Mutual Cooperation and Environmental Awareness of the Sumbergede Village Community, Sekampung District, East Lampung as Character Values ​​in Biology Learning - Riski Rusmalinda; Joni Kawijaya (Public Service: Jurnal Ilmu Sosial dan Pendidikan, 2025)
Biology education should ideally not only convey scientific concepts but also instill character values and environmental awareness. However, in reality, school-based biology learning remains theoretical and lacks local context. The main issue addressed in this study is how to utilize local wisdom particularly the tradition of gotong royong (mutual cooperation) and the community's environmental awareness as a source for strengthening character education in biology learning. This research aims to identify character values within the social and ecological practices of the Sumbergede Village community, located in Sekampung Subdistrict, East Lampung, and to explore their potential integration into biology education. A descriptive qualitative approach was used through observation, interviews, and documentation techniques. The findings reveal that the community's gotong royong practices and ecological habits reflect values of responsibility, social care, and environmental conservation highly relevant to biology topics such as ecosystems, pollution, and biodiversity. Integrating these local values can serve as an effective strategy to foster students’ environmental awareness and character development